A bad moms Christmas [videorecording (Blu-Ray + DVD)] - Lucas, Jon, 1976-; Moore, Scott (Screenwriter); Kunis, Mila, 1983-; Bell, Kristen, 1980-; Hahn, Kathryn, 1974-; Hernandez, Jay, 1978-; Hines, Cheryl; Gallagher, Peter, 1955-; Hartley, Justin, 1977-; Baranski, Christine; Sarandon, Susan, 1946-; Laurence, Oona, 2002-; et al. (Universal Pictures Home Entertainment, 2018)
Follows three underappreciated and overburdened women as they rebel against the challenges and expectations of the Super Bowl for moms: Christmas. If creating a more perfect holiday for their families wasn't hard enough, they have to do all of that while hosting and entertaining their own mothers.